2017
DOI: 10.17843/rpmesp.2017.343.2822
|View full text |Cite
|
Sign up to set email alerts
|

Estrés percibido e intención de migrar al interior del país en médicos y enfermeros que residen en Lima: un análisis exploratorio de la Encuesta Nacional de Satisfacción de Usuarios en Salud (ENSUSALUD), 2015

Abstract: RESUMENObjetivos. Identificar la frecuencia de intención de migrar al interior del país y valorar la asociación entre el estrés percibido (EP) y la intención de migrar al interior del país (IMIP) en médicos y enfermeros que residían en Lima Metropolitana durante el 2015. Materiales y métodos. Análisis secundario de datos, empleando la Encuesta Nacional de Satisfacción de Usuarios en Salud (ENSUSALUD) del año 2015. Se incluyeron únicamente a aquellos profesionales que residían en Lima Metropolitana. Se definió … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Therefore, 18.5% of nurses have displayed depressive symptoms for several days in the previous two weeks. Santiago-Ullero et al 31 found in 2015 that 4.9% of the sample of physicians and nurses living in Lima Metropolitana had the intention to migrate to the interior and that there was an association between perceived stress and the intention to migrate. Marticorena et al 32 found a global prevalence of job burnout of 2.8% using predetermined values; of 7.9% for cut points according to quartiles; and 12.5%, using tertiles.…”
Section: Professional Discomfort and Stressmentioning
confidence: 99%
“…Therefore, 18.5% of nurses have displayed depressive symptoms for several days in the previous two weeks. Santiago-Ullero et al 31 found in 2015 that 4.9% of the sample of physicians and nurses living in Lima Metropolitana had the intention to migrate to the interior and that there was an association between perceived stress and the intention to migrate. Marticorena et al 32 found a global prevalence of job burnout of 2.8% using predetermined values; of 7.9% for cut points according to quartiles; and 12.5%, using tertiles.…”
Section: Professional Discomfort and Stressmentioning
confidence: 99%
“…Esta tiene como propósito explorar la percepción de los usuarios sobre el sistema de salud del Perú (1) , así como algunas reacciones desadaptativas del personal de salud a su contexto laboral, específicamente, la evaluación del burnout (años 2014 y 2016) y el estrés (año 2015) en médicos y enfermeros. De estos se derivaron dos importantes estudios, uno de prevalencia del burnout (2) , y otro sobre el estrés percibido y la intención de migrar al interior del Perú (3) . No obstante, en ningún caso se elaboró de forma previa un análisis psicométrico en la muestra de estudio.…”
unclassified